African swine fever virus structural protein p17 inhibits IRF3 activation by recruiting host protein PR65A and inducing apoptotic degradation of STING - Wang, Shimin; Xiang, Zhiyong; Gao, Peng; Zhang, Yongning; Zhou, Lei; Ge, Xinna; Guo, Xin; Han, Jun; Yang, Hanchun (Frontiers in Microbiology, 2024)
African swine fever virus (ASFV) is notoriously known for evolving strategies to modulate IFN signaling. Despite lots of efforts, the underlying mechanisms have remained incompletely understood. This study concerns the regulatory role of viral inner membrane protein p17. We found that the ASFV p17 shows a preferential interaction with cGAS-STING-IRF3 pathway, but not the RIG-I-MAVS-NF-κB signaling, and can inhibit both poly(I:C)-and poly(A:T)-induced activation of IRF3, leading to attenuation of IFN-β induction. Mechanistically, p17 interacts with STING and IRF3 and recruits host scaffold protein PR65A, a subunit of cellular phosphatase PP2A, to down-regulate the level of p-IRF3. Also, p17 targets STING for partial degradation via induction of cellular apoptosis that consequently inhibits activation of both p-TBK1 and p-IRF3. Thus, our findings reveal novel regulatory mechanisms for p17 modulation of IFN signaling and shed light on the intricate interplay between ASFV proteins and host immunity.